Pertumbuhan Dan Perkembangan Tanaman Sawi Hijau (Brassica Rapa Var) Secara Hidroponik Dengan Pemberian POC (Pupuk Organik Cair) Di UPT Pengembangan Benih Holtikultura - Rahmadina (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
Hydroponics is a farming method in which plant nutrients are provided by a nutrient solution dissolved in water. Hydroponic systems are classified into two types, namely substrate systems and systems without substrate. The media used in hydroponics is organic media. Organic media have different physical and chemical structures compared to inorganic media. This media has durability as a strong support which has a good effect on plants such as being a good nutrients storage place. Green mustard plants with fibrous roots that grow and spread in all directions, no plants form around the soil surface. Mustard greens have short, straight stems that are planted on the ground. The leaves on the green mustard plant are round, glabrous, and light to dark green in color.